Pengaruh Pelayanan, Nisbah Bagi Hasil, Dan Pengetahuan Koperasi Syariah Terhadap Keputusan Menabung Anggota KSPPS BMT Surya Abadi Riyanto Cabang Seputih Raman - Jawoto Nusantoro; Nani Septiana; Fahad (Universitas Muhammadiyah Metro, 2024)
This study aims to determine the effect of service, profit sharing ratio, and knowledge of Sharia Cooperatives on the decision to save members of KSPPS BMT Surya Abadi Riyanto Seputih Raman Branch. There is still a lack of people who decide to save or become members of KSPPS BMT Surya Abadi Riyanto, Seputih Raman branch, which is caused by several factors such as, from the perspective of members who save, there are still many complaints from members regarding poor service, inadequate facilities, and the views of members who are still minimal about Islamic cooperatives. In this study using analytical tools, namely SPSS (Static Package For Social Science). This study uses a type of Quantitative research, with a population of ± 3000 members, and a sample determined using the Slovin formula of 100 respondents. By doing several tests, namely, Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Regression Analysis, t test, F test and Determinant Test (R2). Based on the results of the simultaneous test, it is obtained that the significant value is 0.000 <0.05 and the F-count value is 1231.804> 2.699, which means that there is a simultaneous influence between the Service variable (X1), Profit Sharing Rate (X2), and Sharia Cooperative Knowledge (X3) on the Saving Decision variable (Y). While the figure for R square is 0.975 or 97.5%. This shows that Service, Profit Sharing Rate, and Sharia Cooperative Knowledge have an effect of 97.5% on the Saving Decision of KSPPS BMT Surya Abadi Riyanto Branch Seputih Raman Members. The results showed that simultaneously Service, Profit Sharing Rate and Sharia Cooperative Knowledge had a significant effect on Member Saving Decisions, KSPPS BMT Surya Abadi Riyanto, Seputih Raman Branch should improve Services both in terms of facilities and infrastructure owned such as adding a queuing system, replacing employee support tools that have been worn out, provide a Profit Sharing Rate that is more profitable for members who save, and further educate or provide information so that members and prospective members (the public) have good Sharia Cooperative Knowledge such as products and services offered by KSPPS BMT Surya Abadi Riyanto, Seputih Raman Branch, so as to increase the Decision to Save Members and Prospective Members.